A novel TiO2-SiO2 aerogel nanocomposite absorbent: preparation, characterization and photocatalytic degradation effects on automobile exhaust. (28th February 2018) - Zhang, Saisai; Zhang, Zhengqi; Pei, Jianzhong; Li, Rui; Zhang, Jiupeng; Cai, Jun; Cui, Jiexue
Abstract: In this paper, a novel TiO2 -SiO2 aerogel nanocomposite absorbent was successfully synthesized using the sol-gel and ambient pressure drying method, and its photocatalytic degradation effects on automobile exhaust were investigated for the first time. The microstructures and properties of the Nano TiO2 -SiO2 aerogels were characterized using various methods, including x-ray Diffraction (XRD), Brunauer–Emmett–Teller (BET) specific surface area analysis, Scanning Electron Microscope (SEM), Energy Dispersive Spectroscopy (EDS) and Fourier Transform Infrared Spectroscopy (FT-IR). The exhaust purification tests were conducted in a self-developed instrument to investigate the degradation effects of Nano TiO2 -SiO2 aerogels on automobile exhaust through degradation rate. Experimental results showed that the Nano TiO2 -SiO2 aerogels had a good photocatalytic degradation effect on automobile exhaust, and the degradation rates of CO, CO2, HC and NOx were 1.3%, 1.5%, 3.2% and 34.4%, respectively. The well-designed microstructure makes the Nano TiO2 -SiO2 aerogels a stable photocatalytic material with high specific surface area and big average pore size, which has promising applications in environmental treatment.